Energy production from various biomass wastes via Co-Firing and Photovoltaic-Biogas hybrid systems - Kırım, Yavuz (My University, 2022)
In first part of thesis, modular hybrid renewable energy systems (HRES) comprising of biogas and solar photovoltaic (PV) are designed for various dairy cattle barns located in Konya, Erzurum and İzmir provinces of Turkey. The design also included technical and economic analyses. It is found that the grid-connected system including PV and biomass are more feasible than the stand-alone biomass system in terms of net present cost (NPC), return on investment (ROI), cost of energy (COE) and annual worth (AW). Among the different regression models, ridge regression gives the highest coefficient of determination (R2 ) of 0.92, and the lowest root mean squared error (RMSE) value of 0.463 (million $). Consequently, it is found that total installed cost of solar energy has the strongest effect on the share of electricity generation in terms of the effect on the GDP, which is calculated as 97%. In second part of thesis, a HRES composed of solar photovoltaic and biogas co-firing is designed for a hazelnut cracking plant (HCP) in Ordu province of Turkey. Technical and economic analysis are carried out based on the change in government incentives on renewable sources before (Option A) and after 2021 (Option B) based on NPC and COE. It is found that Option A has the lowest NPC and COE values, which are estimated as 3.00 M USD and 0.098 USD/kW, respectively. In the sensitivity analysis of HRES configuration, total NPC and COE values between nominal discount rate and biomass price generally increase, while the values between expected inflation rate and sellback rate are on a downward trend. Consequently, Scenario-4 has the lowest NPC and COE values, and the highest renewable fraction (RF) at around 73.6%, whereas carbon dioxide (CO2) and nitrogen oxides (NOx)emissions are lowest in Scenario-2.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2022
Keywords: Co-firing; Hybrid renewable energy system; Net present cost; Regression models; Techno-economic analysis